Quarter Life of Crisis in the Millennial Group in terms of Social Comparison and Resilience - Argasiam, Brigitan; Adinda Prabowo Putri, Siska (Universitas Medan Area, 2023)
Quarterlife of crisis (QLC) is becoming a new trend for individuals who are confused about their role in society. The demands of social roles and expectations from the environment are increasing as individuals enter more complex stages of adult life. The tendency of QLC is experienced by many millennials today, especially in Semarang City. The conduct of this study aims to analyze the relationship between social comparison and resilience to quarterlife of crisis in the millennial group. The sample criteria used were aged 22-29 years and lived in the city of Semarang with a sample of 105 people. The sampling technique used is purposive sampling. The research instruments were quarterlife crisis scale (α = .898), social comparison scale (α = .859), and resilience scale (α = .943). The data analysis method used was regression analysis of two predictors and product moment correlation with JASP 0.16 software. The results of this study showed R = 0.919; R2 = 0.845 and F = 279.002 (p < .0001) means that social comparison and resilience affect the quarterlife of crisis in the millennial group. The value of the coefficient of determination of social comparison variables and resilience to quarterlife crisis variables was 84.5%. The conclusion of the study is that social comparison and resilience simultaneously affect the quarterlife crisis. The implications of the results of this study are expected to be useful not only for millennials but also parents and the surrounding community in understanding their condition about their readiness to face the future by not giving much